Arbuscular Mycorrhizal Fungi Alleviate Drought Stress in Trifoliate Orange by Regulating H+-ATPase Activity and Gene Expression - Cheng, Hui-Qian; Zou, Ying-Ning; Wu, Qiang-Sheng; Kuča, Kamil (Frontiers in Plant Science, 2021)
A feature of arbuscular mycorrhiza is enhanced drought tolerance of host plants, although it is unclear whether host H+-ATPase activity and gene expression are involved in the physiological process. The present study aimed to investigate the effects of an arbuscular mycorrhizal fungus (AMF), Funneliformis mosseae, on H+-ATPase activity, and gene expression of trifoliate orange (Poncirus trifoliata) seedlings subjected to well-watered (WW) and drought stress (DS), together with the changes in leaf gas exchange, root morphology, soil pH value, and ammonium content. Soil drought treatment dramatically increased H+-ATPase activity of leaf and root, and AMF inoculation further strengthened the increased effect. A plasma membrane (PM) H+-ATPase gene of trifoliate orange, PtAHA2 (MW239123), was cloned. The PtAHA2 expression was induced by mycorrhization in leaves and roots and also up-regulated by drought treatment in leaves of AMF-inoculated seedlings and in roots of AMF- and non-AMF-inoculated seedlings. And, the induced expression of PtAHA2 under mycorrhization was more prominent under DS than under WW. Mycorrhizal plants also showed greater photosynthetic rate, stomatal conductance, intercellular CO2 concentration, and transpiration rate and better root volume and diameter than non-mycorrhizal plants under DS. AMF inoculation significantly increased leaf and root ammonium content, especially under DS, whereas it dramatically reduced soil pH value. In addition, H+-ATPase activity was significantly positively correlated with ammonium contents in leaves and roots, and root H+-ATPase activity was significantly negatively correlated with soil pH value. Our results concluded that AMF stimulated H+-ATPase activity and PtAHA2 gene expression in response to DS, which resulted in great nutrient (e.g., ammonium) uptake and root growth, as well as low soil pH microenvironment.